2016
DOI: 10.1111/jce.13083
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Associated Genetic Variants and Left Atrial Histology: Evaluation for Molecular Sub‐Phenotypes

Abstract: Among 10 AF-associated SNPs, a single genetic variant was associated with reduced left atrial inflammation, while no histologic differences were observed in the remaining 9. The known AF-associated SNPs do not appear to predispose to the development of pro-inflammatory or pro-fibrotic AF sub-phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Roberts et al . posed a thoughtful integrative approach to the current understanding of genetic causality of disease risk . Moreover, they address an important variable in understanding response to treatment that addresses the risk profile of a patient; specifically the genetic risk profile and its relation to the fibrosis/inflammation that serve as perpetuating substrates for disease.…”
Section: Editorial Commentsupporting
confidence: 56%
See 1 more Smart Citation
“…Roberts et al . posed a thoughtful integrative approach to the current understanding of genetic causality of disease risk . Moreover, they address an important variable in understanding response to treatment that addresses the risk profile of a patient; specifically the genetic risk profile and its relation to the fibrosis/inflammation that serve as perpetuating substrates for disease.…”
Section: Editorial Commentsupporting
confidence: 56%
“…In this issue of Journal of Cardiovascular Electrophysiology , Roberts et al . expand on the above described approaches to pose an important question: is there a way to correlate genetic risk with histopathology of AF, and moreover, is there a role for the evaluation of risk SNPs in further characterizing inflammation and fibrotic mechanisms of the disease? The group selected 10 previously identified SNPs based on disease‐specific prevalence and SNP relationship with genes implicated in AF etiology. Following detailed analysis of inflammation and fibrosis in the left atrial appendage of 177 patients with AF, and correlation with the patient's corresponding SNP, it was found that only one, rs71664883, had a statistically significant association .…”
Section: Editorial Commentmentioning
confidence: 99%
“…No significant association had also been discovered among Chinese Han population in the study performed by Liu et al [27]. However, Roberts et al found that in Caucasian population, the rs7164883 SNP was negatively associated with the inflammation in AF, which was an important pathogenic factor for AF [28]. The divergences might be caused by the diverse genetic backgrounds of the different study populations.…”
Section: Discussionmentioning
confidence: 94%